Answer:
65.434
Step-by-step explanation:
Answer:
bsdjsds
Step-by-step explanation:
<h2>Solving Equations with Absolute Values</h2><h3>
Answer:</h3>
and ![x = -1](https://tex.z-dn.net/?f=x%20%3D%20-1)
<h3>
Step-by-step explanation:</h3>
Solving for the Positive Absolute Value:
![|x -3| = 4 \\ x -3 = 4 \\ x -3 +3 = 4 +3 \\ x = 7](https://tex.z-dn.net/?f=%7Cx%20-3%7C%20%3D%204%20%5C%5C%20x%20-3%20%3D%204%20%5C%5C%20x%20-3%20%2B3%20%3D%204%20%2B3%20%5C%5C%20x%20%3D%207)
Solving for the Negative Absolute Value:
![|x -3| = 4 \\ -(x -3) = 4 \\ -(x -3) \cdot -1 = 4 \cdot -1 \\ x -3 = -4 \\ x -3 +3 = -4 +3 \\ x = -1](https://tex.z-dn.net/?f=%7Cx%20-3%7C%20%3D%204%20%5C%5C%20-%28x%20-3%29%20%3D%204%20%5C%5C%20-%28x%20-3%29%20%5Ccdot%20-1%20%3D%204%20%5Ccdot%20-1%20%5C%5C%20x%20-3%20%3D%20-4%20%5C%5C%20x%20-3%20%2B3%20%3D%20-4%20%2B3%20%5C%5C%20x%20%3D%20-1)
First, let's add all the x's.
x + x + x + x + x = 5x
5x - 1 + 1 + 1 + 1
Now, let's add together all the 1's that are being added (not the 1 that is being subtracted from 5x).
1 + 1 + 1 = 3
5x - 1 + 3
3 - 1 = 2
5x + 2
There's no way you can actually solve this unless you know the value of x; without x's value, this is as simplified as the expression is going to get.
Hope this helps!
when you have a linear combination for example 3x + 2y equals negative 4 you adieu like terms and then multiply